Analisis Pengaruh Tingkat Kemisikinan, Angka Melek Huruf Dan Angka Harapan Hidup Terhadap Indeks Pembangunan Manusia Di Provinsi Sumatera Utara - Harbain, Harbain; Sinurat, Yenni Mariani; Arifin, Indra Welly (Community Service Progress, 2025)
The human development index is measured with povertyrate, the literacy rate,life expectancy. Although The human development index is highly but the poverty still high too, especially in North Sumatera Province at 2012-2023 periods. The method of research is secondary data collecting from North Sumetera and Indonesian central bureau of statistics The result of multiple linier regression which SPSS 26 processing was Y = -142.538 -0.185 X1+1.860 X2+0.444 X3 which means constant value is -142.538 , the influence of poverty rate is negative and not significant a total -0.185, the the literacy rate is positive and significant a total of 1.860 and the influence of the life expectancy is positive and significant a total of 0.444. That is phenomenon of this research. The goal of research is how the influence of the poverty rate , the literacy rate of the and life expectancy against The humand evelopment index in North Sumatera Province.